"Be True to Your School": A 100-Year Legacy of Music Education Faculty at the Indiana University School of Music. Issue 1 (October 2022) - Ward-Steinman, Patrice Madura
The 2020 bicentennial year of Indiana University (IU) Bloomington is a fitting time to recognize the 100-year legacy of the faculty members of the IU Music Education Department. This legacy has not been heretofore documented, exposing a gap in the knowledge of historical traditions and influences. The purpose of this study was to create a comprehensive list of the faculty names, and years of service, and to identify publications, leadership roles, curriculum development, and biographical insights. The historical narrative was created through immersion in the following primary sources found in the IU Archives: The annual Indiana University Bulletins, the Trustees Minutes, and miscellaneous clippings files containing photographs, news items, and obituaries. First edition hard copies of books and published articles by the faculty were examined. Greatest detail is provided for those IU professors of the distant past, including Edward Bailey Birge, Samuel T. Burns, Thurber H. Madison, Jack M. Watson, Dorothy G. Kelley, Newell H. Long, Miriam P. Gelvin, Charles R. Hoffer, and Robert H. Klotman. This study illustrates how one-storied Music Education Department is inextricably linked to its past and suggests that other legacy studies are needed for comparison and contrast.